DEVELOPING KAMISHIBAI MEDIA FOR STORYTELLING NARRATIVE IN MTs AL-JAMI’YATUL WASHLIYAH TEMBUNG - Helmi Juliana Siregar; Sumarsih (Universitas Negeri Medan, 2017)
The aim of this study are: 1) To develop Kamishibai as learning media for storytelling narrative, and 2) to know the eligibility product of Kamishibai as learning media for storytelling narrative. Research and development is used as the research method. This research took place at MTs Al-Jami’yatulWashliyahTembung. The product has validated by experts validation. The instrument for collecting data by using questionnaires with Rating scale 1-5. The data was analyzed based on expert validation to revise the product. The results shows that: 1)the display of media with the average 89,09 (Very good), 2)operation media with the average 85 (very good), 3) interaction when using media with the average 88 (very good), 4) story paper card material with the average 89 (very good). The overall rating is 87,77 (very good). The results of students’ validation are nine from nine respondents answer yes for three aspects that is about the attractiveness, the level of difficulty, and the benefit. Therefore, the product of kamishibai media is appropriate to use as learning media in teaching learning English process.